Faktor – Faktor Yang Menyebabkan Tingginya Tingkat Pelanggaran Lalu Lintas (Studi Pada Dinas Perhubungan Kabupaten Bungo) - Ridwan Ridwan; Siti Maryam; Via Novita (Jurnal Politik dan Pemerintahan Daerah, 2024)
Optimization of factors of high level of traffic violations is Traffic violations often occur due to carelessness, negligence, human intent and lack of legal awareness on the highway. People often ignore traffic signs, even though the meaning of traffic signs is very helpful for people in traffic on the highway, namely the lack of awareness and understanding of the people in Bungo City. The efforts of the transportation agency have been made as much as possible so that traffic violations do not occur. This study aims to determine the factors that cause the high level of traffic violations in Bungo Regency, and the obstacles in reducing the high level of traffic, namely the provision of traffic signs and road equipment by the Bungo Regency Transportation Agency. The method used in this study is a qualitative and quantitative method with a population of 15 sample people. The results of this study indicate that the high level of traffic violations committed by most people in Bungo Regency who have not been able to comply with the applicable regulations, therefore it is necessary to make efforts to reduce traffic violations both directly and indirectly by the Transportation Agency.